Indian Business Groups and Other Corporations Comparative Organisational Perspectives on Indian Corporate Firms - Chakraborty, Achin; Chakraborty, Indrani (India Studies in Business and Economics, 2023)
X, 266 p. 43 illus., 10 illus. in color.